PENIPUAN INFORMASI LOWONGAN KERJA PADA INTERNET DITINJAU BERDASARKAN UNDANG UNDANG NO 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DI SAMARINDA - Amiruddin Amiruddin (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT            The presence of the internet today makes the delivery of information and data becomes faster and infinite space, time and place. This progress is not only give a positive impact to the community but a negative impact on the development of the Internet is by evolving cybercrime, one of the many crimes of cyber crime is fraudulent job information on the internet which rife lately happening in Samarinda because the increase of Internet users in Samarinda. Research issues are about effectiveness of Implementation the regulation number 11 year 2008 about information and electronic transactions toward the doer of fraudulent job information on the Internet especially in Samarinda and protection to the victims of criminal offense fraudulent job information on the Internet especially in Samarinda along roles and responsibility the Department of Communication and Information Technology Samarinda related to fraudulent job information on the Internet.             These research uses descriptive analytical method, a normative juridical approach. The data were analyzed using qualitative descriptive so that the obtained data from the researched could be selected and grouped by quality and truth connected with theory, principles and the rules of law which exists so that it could formulated an answer and legal security to the issues in this essay.             Based on research that has been done, author made a conclusion that effectiveness of Implementation the regulation number 11 year 2008 about information and electronic transactions toward the doer of fraudulent job information on the Internet especially in Samarinda, in fact still not effective caused of the authorities faces many constraints such as human resources, facilities and infrastructure also difficulties to detect the location of the doer of fraudulent job information on the Internet.            The legal protection given to the victims also become ineffective even though inside the regulation number 11 year 2008 about information and electronic transactions especially article 28 paragraph 1 regulated about fraudulent job information on the Internet. Roles and responsibility the Department of Communication and Information Technology Samarinda related to fraudulent job information on the Internet done by a wide range of counseling and delivery about the positive and negative impact of the internet to the whole society also corporate with relevant government agencies such as Regional Office of Manpower Department Samarinda and Head of The County Police the City of Samarinda in an effort to protect the society of Samarinda from criminal offense fraudulent job information on the Internet. Key Word : fraudulent job information on the Internet